La Realidad en la Información Televisada - Pajoni, Hernán (Re-presentaciones: Periodismo, comunicación y sociedad, 2007)
To analyse the impact of television information about the ways realty appears, implies to recover concepts that make explicit the production, circulation and consumption of mass messages, as organizing meanings characte- ristic of the operation of the social system. Then, mass messages do not found societies or dominant thoughts on their own, but they are spaces where hegemonic values are articulated with the historically and culturally determined ways of consumption. On this basis, the informative genre becomes the legitimate discourse about the world of events, forming consumption habits and interpretative models of reality. Moreover, the production routines of the news pro- grammes tend to strengthen a discourse related to the ideal of transparency and objectivity, subordinating the professional act to the logic of the entertainment and the banalization of the complexity of the social events. The journalism training and the professional action should be reconsidered within this context.